Narcissism and consumer behaviour: a review and preliminary findings - Cisek, Sylwia Z.; Sedikides, Constantine; Hart, Claire M.; Godwin, Hayward J.; Benson, Valerie; Liversedge, Simon P. (Frontiers in Psychology, 2014)
We review the literature on the relation between narcissism and consumer behaviour. Consumer behaviour is sometimes guided by self-related motives (e.g., self-enhancement) rather than by rational economic considerations. Narcissism is a case in point. This personality trait reflects a self-centred, self-aggrandizing, dominant, and manipulative orientation. Narcissists are characterised by exhibitionism and vanity, and they see themselves as superior and entitled. To validate their grandiose self-image, narcissists purchase high-prestige products (i.e., luxurious, exclusive, flashy), show greater interest in the symbolic than utilitarian value of products, and distinguish themselves positively from others via their materialistic possessions. Our review lays the foundation for a novel methodological approach in which we explore how narcissism influences eye movement behaviour during consumer decision-making. We conclude with a description of our experimental paradigm and report preliminary results. Our findings will provide insight into the mechanisms underlying narcissists’ conspicuous purchases. They will also likely have implications for theories of personality, consumer behaviour, marketing, advertising, and visual cognition.